2013
DOI: 10.1371/journal.pone.0080487
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Independent Introductions of HIV-1 CRF01_AE Identified in China: What Are the Implications for Prevention?

Abstract: BackgroundHIV-1 CRF01_AE accounts for an important fraction of HIV infections in Asia including China, but little is known about the phylogenetic and evolutionary history of this CRF (circulating recombinant form). In the current study, we collected a large number of 1,957 CRF01_AE gag p17 sequences with known sampling year (1990-2010) from 5 global regions representing 15 countries to better understand the phylogenetic relationships and epidemic history of CRF01_AE strains in China.Methodology/Principal Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
2
14
0
4
Order By: Relevance
“…This study revealed that CRF01_AE was the most prevalent HIV-1 strains among heterosexuals (43.86%) in Jiangsu. In recent years, the persistence of multiple lineages of HIV-1 CRF01_AE strains indicated that certain transmission networks might facilitate the transmission of HIV-1 [25, 26]. Of note, previous studies indicated that patients infected with CRF01_AE had a faster progression to AIDS than with other HIV-1 subtypes, which is associated with a high proportion of X4 tropism [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that CRF01_AE was the most prevalent HIV-1 strains among heterosexuals (43.86%) in Jiangsu. In recent years, the persistence of multiple lineages of HIV-1 CRF01_AE strains indicated that certain transmission networks might facilitate the transmission of HIV-1 [25, 26]. Of note, previous studies indicated that patients infected with CRF01_AE had a faster progression to AIDS than with other HIV-1 subtypes, which is associated with a high proportion of X4 tropism [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…As of late, cases of HIV-1 transmission between neighbouring countries are being reported with increased frequency, due mainly to the greater availability of viral genomic sequences. For instance in China, phylogenetic studies have shown that multiple CRF01_AE lineages circulating in the country were originated from Southeast Asia (Thailand and Vietnam) through independent transmission events [9] [11] . Likewise, purported transmission of subtype C from India to China set off a chain of events including the generation of CRF07_BC and CRF08_BC in China, followed by the sequential migration of CRF07_BC to Taiwan among injecting drug users (IDU) [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Kondo et al 15 reported that there were at least two distinct clades of CRF01_AE among Chinese MSM population, but we can not confirmed they would relate to the same as referred in Feng’s 12 and Abubakar’s study. 16 To define this intra-subtype might be used to provide an argument for extending the official nomenclature to demonstrate the sub-subtype in HIV.…”
Section: Discussionmentioning
confidence: 99%